Characterisation of the alternative sigma factor SigAB in Acinetobacter baumannii - O'Driscoll, Eoghan (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2024)
Acinetobacter baumannii is a priority pathogen and is known to be a leading cause of nosocomial infections worldwide. It is associated with a variety of illnesses including septicaemia, pneumonia, and urinary tract infections (UTIs). It readily acquires resistances to antimicrobials making it extremely difficult to treat in hospital settings. It is an opportunistic pathogen that generally infects people who already have a compromised immune system. A. baumannii survives in a variety of environmental conditions and readily forms biofilms which allow it to persist in hospital settings making it even more dangerous especially due to its capacity to persist on biomedical devices like catheters and ventilators. Despite the dangers posed by A. baumannii, there is still relatively little known about how A. baumannii regulates the expression of various metabolic pathways and how it initiates various stress responses to mitigate environmental stressors. It is crucial to develop a comprehensive understanding of the mechanisms utilised by this bacteria to regulate its metabolism and physiology to adapt to its environment as well as its transcriptional changes in response to various conditions. This knowledge can then be utilised to develop novel treatments and identify drug targets for this pathogen of global concern. One aspect of the regulatory arsenal of A. baumannii that up until now has been understudied are the sigma factor including the alternative sigma factor SigAB. Extra cytoplasmic function (ECF) sigma factors allow bacteria to regulate gene expression by binding to specific promoter regions of the genes in their regulon causing initiation of transcription. ECF sigma factors have been implicated in a variety of biological roles from general stress responses to virulence and antimicrobial resistance. A conserved alternative sigma factor of A. baumannii is SigAB, and this conservation points towards it playing an important role. This study sought to investigate this sigma factor to elucidate its biological function as well as to identify its regulon. A series of phenotypic growth experiments were carried out that identified that a ΔsigAB deletion mutant suffered from a growth defect when exposed to osmotic stressors and detergents. These experiments also identified that the ΔsigAB mutant grew significantly better than wild-type A. baumannii AB5075 when exposed to sub-inhibitory concentrations of chloramphenicol. It was also established that the ΔsigAB mutant suffered no defect in biofilm formation. SigAB is present in A. baumannii across growth stages when grown in rich medium. Transcriptome analysis at late stationary phase, in which SigAB is most abundant in the cell, showed that >300 genes the ΔsigAB mutant were differentially expressed compared to the wild-type AB5075 indicating that it is a global regulator of bacterial gene expression in A. baumannii. Pathway analysis discovered that ATP-synthase biosynthesis and histidine catabolism were significantly downregulated in the deletion mutant. The most down-regulated gene was uncovered to be the uncharacterised small RNA sRNA90 (SabS) and the expression of sRNA90 was independently shown to be dependent on SigAB. Further work indicated that sRNA90 could play a role in regulating multiple hypothetical lipoproteins of unknown function, including ABUW_RS18870. In the heterologous E. coli, it was established that translation of ABUW_RS18870 mRNA was repressed through direct base-pairing with sRNA90. Taken together, an initial characterisation of the alternative SigAB factor showed that it is a global regulator of gene expression mediating resistance to environmental stress and which is directly controlling the expression of sRNA90, which is suggested to act as a post-transcriptional regulator of lipoproteins in A. baumannii AB5075.
APPROVED
Keywords: gram negative; A. baumannii; sigma factors; RNA-seq